THE EFFECT OF FLEXIBLE GROUPING STRATEGY ON THE TENTH GRADE STUDENT’S READING ACHIEVEMENT OF DAARUL AITAM SENIOR HIGH SCHOOL PALEMBANG - Rosmiyati, Evi (Universitas PGRI Palembang, 2020)
The main problem of this study was “Is there any significant effect on the tenth grade students’ reading comprehension achievement after being taught through flexible grouping strategy and those who are not?” Therefore, the objective of this study was to investigate the effect of flexible grouping strategy on the tenth grade students’ reading comprehension achievement of Senior High school students of Daarul Aitam Palembang. This study applied pre-experimental method with pre-test and post-test design. The population of this study was all the tenth grade students of Senior High School of Daarul Aitam Palembang, in the Academic Year of 2019/2020 with the total number 56 students. The sample was 29 students were in experimental group from X IPA. In collecting the data, a multiple choices and true or false test of narrative text was used, and the data were analyzed by using IBM SPSS Statistic. The result of this study showed that the experimental group students’ average score in pretest was 58.7, and in post-test it was 74.05. The value of t-obtained was 300.86 where the value of t-table was 1.70. It was assumed that the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted. Besides that there was significant difference on the eighth grade students’ reading achievement between those who are taught by using flexible grouping strategy and those who are not taught in Senior High School of Daarul Aitam Palembang. The results of using flexible grouping strategy revealed an improvement for students reading achievement. Keywords: Teaching, Reading, Narrative Text, Flexible Grouping